2013
DOI: 10.1021/cb400020b
|View full text |Cite
|
Sign up to set email alerts
|

Launching Spiking Ligands into a Protein–Protein Interface: A Promising Strategy To Destabilize and Break Interface Formation in a tRNA Modifying Enzyme

Abstract: Apart from competitive active-site inhibition of protein function, perturbance of protein-protein interactions by small molecules in oligodomain enzymes opens new perspectives for innovative therapeutics. tRNA-guanine transglycosylase (TGT), a potential target to treat shigellosis, is active only as the homodimer. Consequently, disruption of the dimer interface by small molecules provides a novel inhibition mode. A special feature of this enzyme is the short distance between active site and rim of the dimer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 50 publications
(126 reference statements)
2
34
0
2
Order By: Relevance
“…In a former study, we had shown that the structure of TGT co-crystallized with 4 (TGT∙ 4 co ) reveals a binding mode which is significantly different from that seen in the structure obtained after soaking 4 into an apo-TGT crystal (TGT∙ 4 soak ) (Fig 2 and S2 Fig) [22]. Similar to TGT∙ 3 co , the adopted binding mode in TGT∙ 4 co leads to a pronounced rearrangement of the loop-helix motif accompanied by conspicuous changes of unit cell parameters (reduction of the a -axis and shrinking of the β-angle).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a former study, we had shown that the structure of TGT co-crystallized with 4 (TGT∙ 4 co ) reveals a binding mode which is significantly different from that seen in the structure obtained after soaking 4 into an apo-TGT crystal (TGT∙ 4 soak ) (Fig 2 and S2 Fig) [22]. Similar to TGT∙ 3 co , the adopted binding mode in TGT∙ 4 co leads to a pronounced rearrangement of the loop-helix motif accompanied by conspicuous changes of unit cell parameters (reduction of the a -axis and shrinking of the β-angle).…”
Section: Resultsmentioning
confidence: 99%
“…This technique enables to monitor the oligomerization state of TGT at equilibrium under non-denaturing conditions, in the absence or presence of saturating ligand concentrations [15, 22, 24, 25]. Previously, we found that relative proportions of TGT monomer were strongly dependent on experimental (protein concentration, batch, conditioning) and instrumental settings (cone voltage, backing pressure).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations